1993
DOI: 10.1017/s0003356100006358
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and toxicological evaluation of three deep-stacking methods for the processing of broiler litter as a foodstuff for beef cattle

Abstract: Broiler poultry litter was deep-stacked (2-5 m high) in three ways: (1) uncovered, (2) covered with 0-1524 mm clear polyethylene and (3) surface-watered to form a 2-5 cm crust upon drying. After 30 days, each litter was used to formulate two diets containing proportionately 0-25 or 0-50 poultry litter (dry-matter basis). Urea was used as the nitrogen source in the control diet. All diets contained 100 g/kg cottonseed hulls, 20 g/kg limestone and cracked maize. Each of the seven diets was offered to 12 crossbre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 6 publications
3
9
0
Order By: Relevance
“…This compares well with published values (calculated by difference) of 0.69-0.74 (Bhattacharya & Fontenot, 1966), 0.50 (Rankins et al, 1993) and 0.57-0.58 (Rude & Rankins, 1997). Similarly, the total tract apparent digestibility of OM ranged between 0.54 and 0.64, and compared well with reported OM digestibilities of 0.64 (Fontenot & Jurubescu, 1980), 0.44 and 0.47 (Patil et al, 1995), 0.56 and0.58 (Chaudhry et al, 1996) and 0.42-0.46 (Rossi et al, 1996).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This compares well with published values (calculated by difference) of 0.69-0.74 (Bhattacharya & Fontenot, 1966), 0.50 (Rankins et al, 1993) and 0.57-0.58 (Rude & Rankins, 1997). Similarly, the total tract apparent digestibility of OM ranged between 0.54 and 0.64, and compared well with reported OM digestibilities of 0.64 (Fontenot & Jurubescu, 1980), 0.44 and 0.47 (Patil et al, 1995), 0.56 and0.58 (Chaudhry et al, 1996) and 0.42-0.46 (Rossi et al, 1996).…”
Section: Discussionsupporting
confidence: 91%
“…The potential problems associated with the use of poultry manure or litter as a feedstuff have been investigated extensively. Many studies have emphasised that precautionary measures should be employed when feeding this product, which may be nutritionally unbalanced or pose a health-risk to the animal (Fontenot & Jurubescu, 1980;Fontenot, 1991;Rankins et al, 1993;Mavimbela et al, 1997;Ruffin & McCaskey, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Nutrient composition ofbroiler litter may limit use as a livestock feedstuff. Broiler litter is relatively high (e.g., 24 to 31%) in crude protein Rankins et al, 1993;Goetsch and Patil, 19941, although most nitrogenous compounds in litter are highly soluble and degraded t o ammonia rapidly in the rumen (Goetsch and Patil, 1994). Furthermore, a low quantity of readily available carbohydrate in broiler litter may limit efficiency of nitrogen utilization.…”
Section: Introductionmentioning
confidence: 99%
“…When litter was incorporated into rations for cattle and sheep, it contributed appreciable amounts of Nitrogen. Rankins et al (1993) reported that addition of litter resulted in an overall increase in dietary Nitrogen. The results indicated that 4% urea produced maximum total N as compared to 0% and 2% level.…”
Section: Total Nitrogenmentioning
confidence: 99%